High temperature interactions between K-rich biomass ash and MgO-based refractories. Issue 8 (July 2023) - Wagri, Naresh Kumar; Carlborg, Markus; Eriksson, Matias; Ma, Charlie; Broström, Markus; Andersson, Britt M.
Abstract: MgO-based refractories are used in lime kilns to withstand the high temperature and chemical environment. Efforts to reduce CO2 emissions have led to an increased interest to use bio-based fuels as alternatives to traditional fossil sources. The potential for refractory corrosion from a potassium-rich biomass ash was investigated by studying the infiltration of olive pomace ash into magnesia/spinel refractories. Refractory samples were exposed to the ash at up to 1400 °C for 15–60 min in a CO2 –rich atmosphere. Molten ash infiltrated the refractories through pores and grain boundaries to a depth of up to 9.6 mm, which was quantified with a new systematic procedure. The phase KAlO2 was identified inside the refractories after exposure, indicating an attack of spinel components by potassium. Phases found in the ash residues also indicated the migration of refractory constituents. Thermochemical equilibrium calculations were also used to investigate the ash/refractory chemistry.